2020
DOI: 10.1523/jneurosci.2910-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Development of Dendritic Arbors in Mouse Visual Cortex

Abstract: The dendritic arbor of neurons constrains the pool of available synaptic partners and influences the electrical integration of synaptic currents. Despite these critical functions, our knowledge of the dendritic structure of cortical neurons during early postnatal development and how these dendritic structures are modified by visual experience is incomplete. Here, we present a large-scale dataset of 849 3D reconstructions of the basal arbor of pyramidal neurons collected across early postnatal development in vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 103 publications
(132 reference statements)
1
17
0
Order By: Relevance
“…Our experiments were conducted in juvenile mice (between P21 and P28). Although the dendritic branch structure is static after this age ( Koleske, 2013 ; Richards et al, 2020 ), it is possible that changes in channel composition dampen the effects of dendritic branch structure on excitability. We show that such effects are possible with compartment models ( Figure 7F ), and it is known that changes in dendritic excitability can occur as a result of synaptic plasticity induction ( Frick et al, 2003 ; Frick et al, 2004 ; Losonczy et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments were conducted in juvenile mice (between P21 and P28). Although the dendritic branch structure is static after this age ( Koleske, 2013 ; Richards et al, 2020 ), it is possible that changes in channel composition dampen the effects of dendritic branch structure on excitability. We show that such effects are possible with compartment models ( Figure 7F ), and it is known that changes in dendritic excitability can occur as a result of synaptic plasticity induction ( Frick et al, 2003 ; Frick et al, 2004 ; Losonczy et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent experimental data demonstrate that dendritic growth is affected by synaptic activity ( ), suggesting that changes to dendritic morphology might facilitate dendritic map formation. Since early development is characterized by the establishment of dendritic morphology ( ) and by repeated and rapid synapse turnover ( ; ), it appears as a particularly opportune time for the formation of dendritic maps.…”
Section: Organization Of Excitatory Synapsesmentioning
confidence: 99%
“…Despite the residual amount of expansion and retraction, we showed that morphological stability increases rapidly, and the dendrite morphology is already stable after the initial expansion phase ( Figure 2 d). Interestingly, rapid stabilization of morphology also occurs in the mouse visual cortex ( Richards et al, 2020 ) and the Drosophila larvae ( Castro et al, 2020 ). The rapid slowing down of growth in our model is not due to a depletion of potential synaptic partners as the number of potential synapses remains high ( Figure 2 e).…”
Section: Resultsmentioning
confidence: 99%
“…Here we focus on the early developmental period of highly dynamic growth and retraction. However, dendritic morphology remains remarkably stable in later development and throughout adult-hood ( Richards et al, 2020 ; Castro et al, 2020 ; Koleske, 2013 ). This stability is achieved despite substantial increases in overall size of the animal ( Richards et al, 2020 ; Castro et al, 2020 ) and ongoing functional and structural plasticity of synapses ( Kleindienst et al, 2011 ; Winnubst et al, 2015 ; Kirchner and Gjorgjieva, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation